Multicriteria Optimization of a Dynamic System by Methods of the Theories of Similarity and Criteria Importance - Sergey Misyurin (MDPI AG, 2021)
The problem of multicriteria optimization of a dynamic model is solved using the methods of the similarity theory and the criteria importance theory. The authors propose the original model of a positional system with two hydraulic actuators, synchronously moving a heavy object with a given accuracy. In order to reduce the number of optimizing parameters, the mathematical model of the system is presented in a dimensionless form. Three dimensionless optimization criteria that characterize the accuracy, size, and quality of the dynamic positioning process are considered. It is shown that the application of the criteria importance method significantly reduces the Pareto set (the set of the best solutions). This opens up the possibility of reducing many optimal solutions to one solution, which greatly facilitates the choice of parameters when designing a mechanical object.